Building patient loyalty in the use of telemedicine applications - Andriani, Oktavia; Soelasih, Yasintha (Jurnal Mantik, 2025)
This study aims to analyze the influence of brand image and e-service quality on patient loyalty through patient satisfaction and trust in telemedicine applications. The research utilized a quantitative approach with data collected through online questionnaires distributed to patients in Jakarta who have used telemedicine services. The sample consisted of 202 respondents, and the data were analyzed using Structural Equation Modeling (SEM) via SMART PLS. The results reveal that both brand image and e-service quality significantly impact patient satisfaction, which in turn influences patient trust and loyalty. Additionally, the study confirms that patient trust mediates the relationship between patient satisfaction and loyalty. These findings emphasize the importance of improving service quality and maintaining a positive brand image to enhance patient loyalty in telemedicine platforms. The study suggests that healthcare organizations should focus on optimizing e-service quality, strengthening brand reputation, and ensuring patient satisfaction to foster long-term loyalty in the growing telemedicine sector